Biophysical Dynamics at Ocean Fronts Revealed by Bio‐Argo Floats. Issue 3 (17th March 2023) - McKee, Darren C.; Doney, Scott C.; Della Penna, Alice; Boss, Emmanuel S.; Gaube, Peter; Behrenfeld, Michael J.
Abstract: The straining regions of the ocean in between mesoscale eddies contain large vertical velocities that may be important in regulating phytoplankton accumulation rates. We analyze time series of variables measured by ocean Bio‐Argo floats (mixed layer depths [MLDs], chlorophyll, and carbon concentrations) in conjunction with variables derived from satellite altimetry (strain rates, Lyapunov exponents, vertical velocities) to determine the evolution of mixed layer phytoplankton biomass in response to straining by the mesoscale geostrophic flow. A Lagrangian (water parcel following) framework is justified by restricting the analysis to profiles whose value of a Quasi‐Planktonic Index—an index quantifying averaged distance between a float trajectory and a surface geostrophic trajectory over three consecutive time steps—is less than 5 km. Bin‐averaged Lagrangian derivatives of phytoplankton biomass and chlorophyll concentration are positive for elevated strain rate and upwelling quasigeostrophic vertical velocities. Lagrangian derivatives of MLD and phytoplankton carbon averaged at straining fronts (in rotated along‐ and across‐front coordinates) have features in common with submesoscale dynamics, including increasing phytoplankton carbon (and chlorophyll) and a shoaling mixed layer over the front. To elucidate a mechanism, we average time derivatives of modeled cell division rates, finding the pattern approximately matches the pattern of phytoplankton accumulation rates and is controlled primarily by the term modulating light stress, suggesting that frontal dynamics cause accelerations of division rates by increasing available light. Regions of increasing chlorophyll are also approximately co‐located with upwelling quasigeostrophic velocity, suggesting non‐Lagrangian behavior of floats causes some imprint of larger scale, more persistent mesoscale signals. Plain Language Summary: When mesoscale eddies (large, swirling flows) interact in the ocean, the currents at their edges strain tracers. Straining sharpens horizontal density gradients, disrupting force balances and causing large vertical velocities that can accelerate division rates of phytoplankton (small, drifting photosynthetic organisms) by supplying them with nutrients or bringing them closer to light. Bio‐Argo floats measure vertical profiles of temperature and salinity (constituents of seawater density) and backscattering (proportional to phytoplankton biomass) as they drift with currents. By evaluating time rates of change of these variables along a float track and collocating float profiles in space and time with straining fronts (identified from satellite altimetry), we obtain a picture of how phytoplankton evolve in response to strain. We find that straining fronts are characterized by increasing density stratification and biomass on the anticyclonic side of, and above, straining fronts, largely consistent with theoretical expectations. Further, by comparing with a model of cell division rates, we find increases in biomass at straining fronts are primarily due to increases in available light. With a larger data set of closely spaced float profiles, our methodology could clarify the importance of straining regions in the carbon cycle. Key Points: Positive phytoplankton accumulation rates are associated with elevated geostrophic strain and quasigeostrophic upwelling Averaged Lagrangian derivatives at straining fronts include positive accumulation rates and a shoaling mixed layer on the less dense side Frontal dynamics drive increases in phytoplankton biomass by accelerating cell division rates primarily through increased available light